A novel approach for capturing and evaluating dynamic consumer requirements in open design. (January 2019) - Li, Shipei; Tang, Dunbing; Yang, Jun; Wang, Qi; Ullah, Inayat; Zhu, Haihua
Abstract: In the product design, understanding consumer requirements (CRs) is essential due to the fact that it influences the success of the product. Currently, it has been recognized that consumer involvement in an open design (OD) environment is an effective way to reduce the gap between what is required by consumers and what companies can provide. In the process of OD, the initial CRs may shift as the consumers can influence each other, and it is a challenge to capture and evaluate dynamic CRs in OD. In this study, the dynamic relationship between consumers who participate in OD is discussed based on Nash equilibrium. Corresponding to the dynamic relationship, a novel approach is proposed to explore the crucial CRs from consumers' perspective. Initially, the platform of OD is constructed on the Internet to collect the CRs and its evaluations. Thereafter, a similarity-based filtering method (SFM) is presented to filter out the most differentiated evaluations. Furthermore, to get the weight of the CR evaluated by consumers, an improved fuzzy Delphi method is introduced. Meanwhile, to solve the problem of excessive number of CRs, a dual-index evaluation method is put forward to control the opening degree of OD. Finally, to demonstrate the applicability of the suggested approach, a product of smartphone is examined as a case study. The results confirm that the proposed approach is appropriate for capturing and evaluating dynamic CRs in OD.